CD4+ T Cell Defects in a Mulibrey Patient With Specific TRIM37 Mutations - Bruzzaniti, Sara; Cirillo, Emilia; Prencipe, Rosaria; Giardino, Giuliana; Lepore, Maria Teresa; Garziano, Federica; Perna, Francesco; Procaccini, Claudio; Mascolo, Luigi; Pagano, Cristina; Fattorusso, Valentina; Mozzillo, Enza; et al. (Frontiers in Immunology, 2020)
Mulibrey (muscle-liver-brain-eye) syndrome (MUL) is an autosomal recessive disorder caused by mutations in the TRIpartite motif (TRIM)37 gene, encoding for TRIM37 a member of the TRIM E3 ubiquitin ligase protein family. MUL patients are characterized by growth retardation, dysmorphic features and a wide range of abnormalities affecting different organs. However, T-cell abnormalities have not been observed in MUL subjects, to date. Here we described the immunological features of a MUL child carrying recently identified TRIM37 mutations, a 17q22 deletion of maternal origin combined with a TRIM37 variant of paternal origin. Here we found quantitative and functional defects in CD4+ T cells from this MUL case. Low levels of TRIM37 protein were specifically detected in CD4+ T cells of MUL patient and associated with their altered proliferation and cytokine production. Of note, both CD4+ and CD8+ T lymphocytes of MUL child displayed an effector memory phenotype compared with healthy children. This clinical case research highlighted the possible role of TRIM37 in the control of immune cell number and function, especially in CD4+ T cells. Finally, this study may open the way to novel mechanistic studies aim at identifying in depth the role of TRIM37 protein in the immune system.